Distributed voltage unbalance compensation for an islanded microgrid system in a sensitive load bus - Han, Ziying (2016)
This project demonstrated a distributed voltage unbalance compensation scheme for an islanded microgrid system with main consideration of a sensitive load bus. A hierarchical control structure is commonly used for voltage unbalance compensation. Realization of voltage unbalance compensation in this project is to propose a cooperative and distributed compensation strategy. A two-layer secondary compensation controller is designed for each local Distributed Generator (DG). It consists of a communication layer and a compensator layer, as well as a new concept of Contribution Level is introduced to illustrate the compensation ability for a certain DG. A cooperatively distributed secondary control requiring information sharing is proposed based on the finite-time average consensus algorithm and a graph detection algorithm. The algorithms applied can fulfill the compensation within finite time and execute information sharing without knowing the structure as prior. The distributed secondary compensation is able to perform the similar compensation ability as centralized secondary structure; meanwhile, there are also improvement for special conditions including communication fault and plug-and-play. Simulations are carried out in Matlab Simulink environment, and cases involving communication failure, CL shift, and DG plug-out are tested and analyzed to verify the practicability of proposed design.